2011
DOI: 10.1083/jcb.201106098
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of a novel compartment for autophagosome-mediated unconventional protein secretion

Abstract: A novel membrane structure called CUPS is assembled during the secretion of unconventional cargo such as Acb1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(249 citation statements)
references
References 57 publications
(91 reference statements)
8
220
2
3
Order By: Relevance
“…Studies have primarily focused on autophagy in unconventional secretion, a collection of processes through which certain proteins are secreted from cells either via direct trafficking from the endoplasmic reticulum (ER) to the plasma membrane in a Golgi-independent manner, or via the transport of cytoplasmic proteins lacking an amino-terminal ER signal sequence to the cell surface, completely bypassing the ER-Golgi route 126 . Autophagy-related proteins (ATGs) have been genetically implicated in the unconventional secretion of the acyl-CoA-binding protein Acb1 in yeast (AcbA in Dictyostelium discoideum), and inflammatory mediators such as interleukin-1β (IL-1β) and IL-18, the high mobility group protein B1 (HMGB1) and the integral membrane protein ΔF508 CFTR (cystic fibrosis transmembrane conductance regulator) in mammalian cells [127][128][129][130][131] . The unconventional secretion of these proteins is also dependent on Golgi membrane-binding proteins of the GRASP family in both yeast and mammals 129,130,132 .…”
Section: Box 2 | Autophagy and Secretionmentioning
confidence: 99%
“…Studies have primarily focused on autophagy in unconventional secretion, a collection of processes through which certain proteins are secreted from cells either via direct trafficking from the endoplasmic reticulum (ER) to the plasma membrane in a Golgi-independent manner, or via the transport of cytoplasmic proteins lacking an amino-terminal ER signal sequence to the cell surface, completely bypassing the ER-Golgi route 126 . Autophagy-related proteins (ATGs) have been genetically implicated in the unconventional secretion of the acyl-CoA-binding protein Acb1 in yeast (AcbA in Dictyostelium discoideum), and inflammatory mediators such as interleukin-1β (IL-1β) and IL-18, the high mobility group protein B1 (HMGB1) and the integral membrane protein ΔF508 CFTR (cystic fibrosis transmembrane conductance regulator) in mammalian cells [127][128][129][130][131] . The unconventional secretion of these proteins is also dependent on Golgi membrane-binding proteins of the GRASP family in both yeast and mammals 129,130,132 .…”
Section: Box 2 | Autophagy and Secretionmentioning
confidence: 99%
“…This conclusion, however, is not supported by ultrastructural observations, and therefore, the nature of the carriers transporting Acb1 remains to be deciphered. Nonetheless, electron microscopy work in S. cerevisiae has revealed that the initial precursor structure of this transport route is a cluster of membranes and vesicles, which morphologically resemble the precursor structures involved in autophagy (Mari et al 2010), and they are positive for both Atg8 and Atg9 (Bruns et al 2011).…”
Section: Noncanonical Autophagymentioning
confidence: 99%
“…Another factor required for this process is Grh1, the yeast homolog of the mammalian Golgi reassembly and stacking protein (GRASP), which has been implicated in various types of unconventional secretion (Nickel and Rabouille 2009). As discussed above, while the nature of the carrier transporting Acb1 remains to be determined, a precursor structure named the compartment for unconventional protein secretion (CUPS) has been characterized (Bruns et al 2011). This organelle, in close proximity to the ER exit sites and onto which Acb1 is recruited upon nitrogen starvation, is positive for Grh1, Atg8, Atg9, and Vps23, one of the components of the endosomal sorting complex required for transport (ESCRT), as well as PtdIns3P.…”
Section: Unconventional Protein Secretionmentioning
confidence: 99%
“…Autophagy, and autophagy-related processes, also function in biosynthetic modes including the delivery of resident vacuolar hydrolases 1 and unconventional protein secretion. [2][3][4] The degradative autophagic pathway involves the sequestration of cytoplasm into double-membrane vesicles, termed autophagosomes, which fuse with the vacuole, releasing the inner membrane vesicles and cargo into the vacuolar lumen for degradation. 5 Autophagy was first identified in yeast as a starvation response essential for overcoming conditions of nutrient deprivation; however, in multicellular organisms, aside from its role in cellular homeostasis, autophagy is required for processes as diverse as the removal of protein aggregates and damaged or superfluous organelles, development and cellular remodeling, and immunity.…”
Section: Introductionmentioning
confidence: 99%